The Influence of Sectoral and Regional Economic Interests on Russian Legislative Behaviour: The Case of State Duma Voting on Production Sharing Agreements Legislation - Chaisty, P (Bellwether Publishing, 2007)
Abstract: A political scientist examines legislation on production sharing agreements. Through the analysis of contested roll call voting on this issue during Russia’s first three Dumas (1995–2001), the period when legislation was first enacted and lobbying was allegedly at its height, the degree to which a distinct and coherent set of economic interests influenced voting is estimated. The question of whether there were systematic linkages between economic interests—sectoral (private business and state) and regional— and the voting behavior of Duma deputies is considered. Research results are used to discuss the Russian parliament’s capacity to articulate and integrate interests in ways that further the public good."